.5(3x-4)-.7=.4(5+4x)

Simple and best practice solution for .5(3x-4)-.7=.4(5+4x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .5(3x-4)-.7=.4(5+4x) equation:


Simplifying
0.5(3x + -4) + -0.7 = 0.4(5 + 4x)

Reorder the terms:
0.5(-4 + 3x) + -0.7 = 0.4(5 + 4x)
(-4 * 0.5 + 3x * 0.5) + -0.7 = 0.4(5 + 4x)
(-2 + 1.5x) + -0.7 = 0.4(5 + 4x)

Reorder the terms:
-2 + -0.7 + 1.5x = 0.4(5 + 4x)

Combine like terms: -2 + -0.7 = -2.7
-2.7 + 1.5x = 0.4(5 + 4x)
-2.7 + 1.5x = (5 * 0.4 + 4x * 0.4)
-2.7 + 1.5x = (2 + 1.6x)

Solving
-2.7 + 1.5x = 2 + 1.6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1.6x' to each side of the equation.
-2.7 + 1.5x + -1.6x = 2 + 1.6x + -1.6x

Combine like terms: 1.5x + -1.6x = -0.1x
-2.7 + -0.1x = 2 + 1.6x + -1.6x

Combine like terms: 1.6x + -1.6x = 0.0
-2.7 + -0.1x = 2 + 0.0
-2.7 + -0.1x = 2

Add '2.7' to each side of the equation.
-2.7 + 2.7 + -0.1x = 2 + 2.7

Combine like terms: -2.7 + 2.7 = 0.0
0.0 + -0.1x = 2 + 2.7
-0.1x = 2 + 2.7

Combine like terms: 2 + 2.7 = 4.7
-0.1x = 4.7

Divide each side by '-0.1'.
x = -47

Simplifying
x = -47

See similar equations:

| 8b+3(2b+2)=11 | | 8v-12+5v=5v+10-3v | | 7(3x-1)=5+4(x-3) | | -4k-8+11=-3k-12 | | -16x=-8 | | 3x^2+12x-61=0 | | 3x^2+36+105= | | -7+4(3a+1)=-7 | | 8+7x=109 | | 6/5+3/5x=61/30+7/6x+1/6 | | -7x-9y=-3 | | 1/6(6y+12)-9=-1/4(12y-20) | | 7=2x/5 | | 3x+6-x=69 | | 89-(5x+13)=5(x+2)+x | | 5d-2(6d+5)=5-(10+10d) | | 3-2lnx=8 | | -113=7+10x | | 7/6x+3x/5 | | 34=16*x-14 | | 6(3+2x)-1=65 | | a+(b^2)*3c-2d= | | (9ab+7cd)*3e= | | r+0.10=760 | | 9ab+7cd= | | 30=-5/4x | | m=19-5(x-n) | | 5a+4b+3c+4d+3e= | | 5a*4b*3c*4d*3e= | | r/2+0.6r=247 | | 2a-3b=12 | | 8-2(t-1)=t+7 |

Equations solver categories